Time to Tangle Questions (2011)
EAFIT Children's University launches two new initiatives. The first is the Questions Network, which seeks to invite children to ask themselves questions and to seek answers to them. The second consists of a science writing workshop for children and young people so that they develop skills and tools to answer their questions and those of other children.